Optimizing the Synchronization of Multiple Bus Routes at Multiple Transfer Points Assuming Stochastic Bus Journey Times - (:unkn) unknown (My University, 2014)
In this thesis, we develop a discrete event simulation model of a generic bus transit system in which transfers of passengers between bus routes are considered at all bus stops in the network. The model considers several real-world aspects including stochastic passenger demand and stochastic bus travel times. Transfers of individual passengers between bus routes are explicitly modeled. The model shows how different values for the decision variables - the route assigned to each bus and the timetable for each bus - affect the time an average passenger spends in the system and other performance measures. In the experiments, we use simulation optimization to identify "near-optimal" bus routes, bus start times, and bus scheduled travel times that minimize average passenger time in the system. Results from the experiments show that well synchronized bus schedules - that allow passengers to transfer between different bus routes with little or no waiting time - can improve the overall performance of the system.